SEROLOGICAL MONITORING OF NEWCASTLE DISEASE IN RUSSIA 2017 - M. A. Volkova; Ir. A. Chvala; P. S. Yaroslavtseva; V. Yu. Sosipatorova; I. A. Chvala (Ветеринария сегодня)
Newcastle disease is an OIE-listed and highly contagious viral avian disease inflicting great economic losses and constituting a serious threat to poultry farms all over the world. The paper provides monitoring research results for Newcastle disease among poultry and wild birds in the Russian Federation for 2017. The tests were carried out with diagnostic kits for Newcastle disease virus antibody detection by immunosorbent assay and HI at the FGBI “ARRIAH” Reference Laboratory for Viral Avian Diseases (Vladimir). Biological material delivered from Rosselkhoznadzor Territorial Administrations was collected from 31 678 domestic and 433 wild and synanthropic birds from 22 and 4 regions of the Russian Federation, respectively. The paper shows different levels of seroprevalence in poultry from industrial poultry establishments of a closed type and backyards and in wild birds of various regions of the Russian Federation. Almost total Newcastle disease seroprevalence was found in adult poultry from industrial closed establishments due to a total vaccination against the disease. Broilers demonstrated a relatively low average Newcastle disease virus seroprevalence because of an insufficient antibody level by the moment of blood sampling (mostly during slaughter). On average, antibodies to Newcastle disease virus were detected in one third of samples from backyard poultry. With that, high seroprevalence was registered on farms of North Caucasian Republics and southern regions of the Russian Federation. Seroprevalence in wild birds was moderate. Thus, the monitoring research indicates an unstable epidemiological situation for Newcastle disease in the Russian Federation and the remaining risk of disease outbreak on industrial and backyard farms.